Processing milk causes the formation of protein oxidation products which impair spatial learning and memory in rats. Issue 39 (17th July 2019) - Li, Bowen; Mo, Ling; Yang, Yuhui; Zhang, Shuai; Xu, Jingbing; Ge, Yueting; Xu, Yuncong; Shi, Yonghui; Le, Guowei
Abstract : Eating a high protein oxidation diet leads to oxidative stress, leading to spatial learning and memory impairment. Dairy products processing conditions should be regulated to control the oxidation level of proteins, improve eating habits, and avoid damage to human health. Abstract : This study explored the effects of protein oxidation during milk processing on spatial learning and memory in rats. Increasing the heating time, fat content, and inlet air temperature during processing by boiling, microwave heating, spray-drying, or freeze-drying increases milk protein oxidation. Oxidative damage done to milk proteins by microwave heating is greater than that caused by boiling. Dityrosine (DT), as a kind of tyrosine oxidation product, is the most important marker of this process, especially during spray-drying. Rats received diets containing either SWM (spray-dried milk powder diet), FWM (freeze-dried milk powder diet), FWM + LDT (freeze-dried milk powder + low dityrosine diet, DT: 1.4 mg kg −1 ), or FWM + HDT (freeze-dried milk powder + high dityrosine diet, DT: 2.8 mg kg −1 ) for 6 weeks. We found that the SWM group, the FWM + LDT group, and the FWM + HDT group appeared to have various degrees of redox state imbalance and oxidative damage in plasma, liver, and brain tissues. Further, hippocampal inflammatory and apoptosis genes were significantly up-regulated in such groups, while learning and memory genes were significantly down-regulated. Eventually, varying degrees of spatial learning and memory impairment were demonstrated in those groups in the Morris water maze. This means that humans should control milk protein oxidation and improve the processing methods applied to food.